Development of a Self Management Module to Improve Student Learning Discipline at MAN 1 Lebak - Sabila, Alfira Putri; Rochani, Rochani; Rahmawati, Rahmawati; Dwinurnala, Meilla (IAIN Kudus, 2024)
Development of a Self Management Module to Improve Student Learning Discipline at MAN 1 Lebak. This research and development aims to determine the development of the Self Management module in improving student learning discipline, the phenomenon of undisciplined learning behavior in schools makes researchers worried about the future of students, the need for media development that is able to minimize these problems, and one of them is using media. a self-management module that can be used as a reference for guidance and counseling teachers in dealing with learning discipline problems. As mentioned above, this research is research that uses the research and development method or research and development with the ADDIE development model or analysis, Design, Development, Implementation and Evaluation. The data collection technique in this research used data analysis in the form of distributing learning discipline questionnaires to 71 students, of which 14 students or 19.7% were in the high category, then 24 students or 33.8% of students were in the medium category and there were 33 students or 46 % categorized as low. Furthermore, a feasibility test was carried out with media, material and practitioner experts and the average score was 88% or in the very suitable for use category. Furthermore, the module was tested on a limited basis with 7 students who were detected to have a low level of learning discipline. And it was found that the average percentage of N-gain was 80.62% or categorized as effective in helping students improve their learning discipline.Keywords: Module, Self Management, Learning Discipline